The role of conflict in continuity and change: life events associated with identity development in racially and ethnically diverse women - Anthis, Kristine (Identity, 2011)
In this archival study, life events were identified that served as precursors to identity transitions in 149 European American, African American, Mexican American, and Puerto Rican women. The data were collected during a period from the late 1970s to the early 1980s in the United States. Participants were interviewed and asked to describe events that had influenced their understanding of themselves. Events were coded into relational, career, education, personal, health-related, and miscellaneous categories. Results indicated that women were more likely to report life events regarding their relationships than events in other categories. A reexamination of the data revealed that that there were more similarities than differences among the racial and ethnic groups in terms of the life events described. Respondents were more likely to report continuity than change in their identities in response to life events serving as possible precursors to change. Results also revealed that when change did occur, it was associated with high levels of conflict particularly for the domains of relationships and educational achievement expectations. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy